Analisis Penyebaran Fasilitas Pendidikan dan Dampaknya Terhadap Peningkatan Kualitas Sumber Daya Manusia di Kabupaten Pasaman Barat - Aulia Rahmah, Rosi (Bertuah Jurnal Syariah dan Ekonomi Islam, 2023)
The distribution of educational facilities evenly plays an important role in improving the quality of human resources (HR) in a region. This study aims to analyze the distribution of educational facilities in West Pasaman Regency and its impact on improving the quality of HR. The research method used is quantitative descriptive with primary and secondary data obtained through surveys, interviews, and data from related agencies. The results of the study indicate that the distribution of educational facilities in West Pasaman Regency is still uneven, especially in rural areas that have limited access to educational facilities. This inequality has an impact on the disparity in the quality of education between urban and rural areas, which ultimately affects the quality of HR. Therefore, strategic policies are needed from the local government to accelerate the development of evenly distributed educational facilities, especially in disadvantaged areas, in order to create quality and competitive HR.